PROYEK DIGITALISASI NASKAH SEBAGAI UPAYA PELESTARIAN KEKAYAAN BUDAYA INDONESIA - Nur Afifah, Dewi (Universitas PGRI Palembang, 2024)
The manuscript is a handwriting that has become one of the nation's cultural treasures. Therefore, the existence of manuscripts in a country, especially in Indonesia, is very impactful for research purposes in obtaining accurate information. However, the existence of these manuscripts is still widespread among the public so that their ownership is recognized by individuals. This certainly has an impact on the condition of the manuscript which is prone to damage due to improper care and even just left alone by the owner without any effort to protect and maintain. In addition to these impacts, this problem will also make it difficult for a philologist to conduct research considering that manuscripts are the only object of study used. In this case, various efforts to preserve the manuscript should be improved. One of the efforts that can be done as an alternative way is to utilize technology such as digitalization projects. In addition to preserving the manuscript, this step also aims to allow the next generation to know and learn various histories as outlined in the ancient texts of the archipelago. Keywords: manuscript, culture, philological research, digitization project